Highly Selective Synthesis of a-Bromoesters Using Molecular Bromine Catalyzed by Phosphorus - Sun, Zhaoyun; Peng, Xinhua; Dong, Xiongzi; Shi, Wenwen (Asian Journal of Chemistry, 2011)
A series of a-bromoesters have been synthesized by applying Hell-Volhard-Zelinsky reaction catalyzed by phosphorus instead of usual phosphorus tribromide. An excellent regioselectivity to good yields are achieved at comparatively mild reaction conditions of an operational simplicity.